Green economic growth from a developmental perspective - Bei Jin; Gang Li (China Finance and Economic Review, 2013)
This paper discusses the relationship between industrial development and environmental protection. The paper argues that human beings cannot solve the problems linked to the environment and the natural resources in a stagnant manner, nor can human beings achieve sustainable development in the extensive economic growth model of ignoring resource constraints and the environment. The difficulties of China's environmental protection lie in the balance of the relationship between the reform of regulation governing resources and the environmental and the international competitiveness of China's industrial sector, in particular, the balance of the relationship between environmental protection and economic growth. China's industrialization practices show that the country's industrial sector itself has the potential to help promote the improvement of the utilization efficiency of resources and the environment. At the same time, however, it can consume significant resources, causing certain environmental degradation. Industrial processes can have negative environmental impacts, but industrial development can play a positive role in environmental protection and improvement from a global and long-term perspective. It is impossible for China to solve the problems linked to resources and the environment without the development of industrial entities. On the contrary, the pressure on the resources and the environment can only be relieved with more advanced and powerful industries. In China, public opinion on environmental protection has been formed and will become stronger. Therefore, we have reason to be optimistic for the country's environmental protection and improvement.
Keywords: 330; Environmental protection; Industrial development; Green economy